Penatalaksanaan Fisioterapi Pada Pasien Dengan Cerebral Palsy Flaccid Hipotonus Quadriplegi Tipe Ekstensi dengan Metode Neuro Senso Motor Reflex Development and Synchronization dan Neuro Development Treatment - Muazarroh, Salma; , Totok Budi Santoso, S.Fis., MPH (2017)
Background: Cerebral Palsy is a non-progressive brain disorder that occurs during prenatal, perinatal, postnatal and during growth and development is usually a problem with motor control, sensory and postural control. In such cases it can be performed with physiotherapy modalities such as Neuro Senso Motor Reflex Development and Synchronization for sensory problems and Neuro Development Treatment for the motor to be independent independent of others Objective: To know the implementation of Physiotherapy in increasing sensory and functional or motor ability in cerebral palsy case using Neuro Senso Motor Reflex Development and Synchronization and Neuro Development Treatment modality. Result: after therapy for 6 times the result of muscle strength there is no change of shoulder region, elbow, wrist result X while for hip, knee, ankle result Trace. Sensory no change of all components still value 1. Reflex there is an increase from the level of brain stem up to mid brain. Functional ability there is a change of 0.2%. Conclusion: Modality Neuro Senso Motor Reflex Development and Synchronization and Neuro Development Treatment can be used to train the sensory and functional abilities even though the result is not significant because it must be balanced with the intensity of the exercise routine.